FORMULASI MASKER GEL PEEL OFF EKSTRAK DAUN SAGA (Abrus precatorius L.) VARIASI BASIS GEL - Putra, Marzela Pancaya; Afriliya, Ayu; Tanafasa, Diana; Boan, Margareta Debyani; Arimbi, Nindyasiwi; Nurkharimah, Vivin (Jurnal Farmasi Klinik dan Sains, 2024)
Saga leaves (Abrus precatorius L.) have antioxidant properties contained in flavonoid compounds so they can inhibit free radicals in dry skin. The aim of this research was the formulation and physical evaluation of saga leaf peel-off gel mask preparations, as well as the effect of variations in gelling agents on physical evaluations in the form of organoleptics, homogeneity, pH, spreadability, stickiness and drying time. The method in this research is that saga leaves are extracted using the maceration method. Variations in the gel base are in three formulas, namely HPMC 4%, Karbopol 1%, and CMC Na 3%. The research results showed that the peel off gel mask was homogeneous, had a green color, a distinctive odor, a semi-thick texture, the pH values were F1 = 6.68, F2 = 6.73 and F3 = 4.90;  adhesion power F1 = 3.46 seconds, F2 = 3.65 seconds and F3 = 20.27 seconds; spreading power F1 = 3.23 cm, F2 = 2.33 cm, and F3 = 2.25 cm; Drying time F1 = 19.3 minutes, F2 = 8.96 minutes, and F3 = 9.25 minutes. The hedonic test results of the three formulas that were most liked by the panelists based on color, aroma, texture and drying time were formula 1 which used a 4% HPMC gel base. SPSS data using One Way ANOVA, variations in the gelling agent in the peel off gel mask preparation had a significant influence on pH, stickiness, spreadability and drying time.